Sustainable construction, Volume 17, Issue 5 : Action for sustainability in the Mediterranean region. - Sinou, Maria (Management of Environmental Quality: An International Journal., 2006)
This e-book is dedicated to the presentation of key articles and main outcomes of the International Conference SB04MED, "Sustainable construction: action for sustainability in the Mediterranean region". As well as being a regional precursor to the Global SB05 Conference in Tokyo, the conference provided an arena for the dissemination of the LIFE "SB-MED" Project: "Enhancing transferability of innovative techniques, tools methods and mechanisms to implement sustainable building in the Mediterranean basin."